Resiliensi Masyarakat Desa Batuan Kabupaten Gianyar pada Sektor Pariwisata Pasca Covid-19 - Kusuma, Bima Oktadinata; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
The decline in the number of tourists and the closure of tourist areas have made the tourism sector, which was originally a source of livelihood for the people of Batuan Village, no longer able to provide the same contribution compared to before the Covid-19 pandemic. Community resilience is needed to face of environmental changes that have an impact on disasters. This study aims to determine the resilience of the Batuan Village community, Gianyar Regency in the tourism sector after Covid-19. The research method used in this research is descriptive qualitative. Collecting data through the methods of observation, interviews, and documentation. The analysis uses the theory of community resilience according to Norris et al. (2008). The findings show that the people of Batuan Village, Gianyar Regency are resilient in dealing with the impact of Covid-19 on the tourism sector. Batuan Village through understanding resources in identifying problems and planning as well as how to deal with problems, and creativity and flexibility the ability to adapt to change, ready to accept new things in overcoming the impact of Covid-19.